Comparative Research of Antioxidant, Antimicrobial, Antiprotozoal and Cytotoxic Activities of Edible Suillus sp. Fruiting Body Extracts - Asta Judžentienė; Jonas Šarlauskas (Foods)
The aim of this study was to evaluate bioactive properties of Basidiomycota fungi, mainly Suillus sp. Wide spectrum of activities were revealed for S. variegatus, S. luteus, S. bovinus and S. granulatus; and obtained results were compared with other common fungi. Total Phenolic Content (TPC) varied from 245.32 ± 5.45 to 580.77 ± 13.10 (mg (GAE) per 100 g of dry weight) in methanolic extracts of S. bovinus and S. granulatus fruiting bodies, respectively. In ethyl acetate extracts, the highest TPC were obtained for S. variegatus (310 ± 9.68, mg (GAE)/100 g, dry matter), and the lowest means for S. luteus (105 ± 3.55, mg (GAE)/100 g dry weight). The ethyl acetate extracts of the tested Suillus species exhibited a stronger antioxidant activity (AA) to scavenge DPPH● and ABTS•+ than the methanolic ones, and the highest effects were determined for S. luteus (EC50, 0.15 ± 0.05 and 0.23 ± 0.05%, respectively). In the case of methanolic extracts, the highest AA were evaluated for S. granulatus. (EC50 for DPPH● and ABTS•+, 0.81 ± 0.30 and 0.95 ± 0.22%, respectively). The ABTS•+ scavenging potential varied from 0.25 ± 0.05 to 0.74 ± 0.10 (mmol/L, TROLOX equivalent, for S. granulatus and S. variegatus fruiting body extracts, respectively) in the ethyl acetate extracts. S. granulatus extracts demonstrated the widest range of antimicrobial effects against both gram-positive and gram-negative bacteria (from 11.7 ± 1.3 to 28.5 ± 3.3 mm against Pseudomonas aeruginosa and Bacillus mycoides, respectively); and against two fungal strains (up to 13.6 ± 0.4 mm on Meyerozyma guilliermondii) in agar disc diffusion tests. Our study revealed that methanolic extracts of the most tested Suillus sp. were not active enough against the tested parasites: Trypanosoma cruzi, Trypanosoma brucei, Leishmania infantum and Plasmodium falciparum. Only S. variegatus extracts showed good antiprotozoal effects against P. falciparum (12.70 µg/mL). Cytotoxic activity was observed on human diploid lung cells MRC-5 SV2 by S. granulatus extracts (64.45 µg/mL). For comparative purposes, extracts of other common Lithuanian fungi, such as Xerocomus sp. (X. badius, X. chrysenteron and X. subtomentosus), Tylopilus felleus, Phallus impudicus and Pycnoporus cinnabarinus were investigated for their activity. The P. cinnabarinus extracts demonstrated the highest and broadest overall effects: 1.32 µg/mL against T. brucei, 1.46 µg/mL against P. falciparum, 3.93 µg/mL against T. cruzi and 21.53 µg/mL against L. infantum. Additionally, this extract exhibited strong cytotoxicity on MRC-5 cells (13.05 µg/mL). The investigation of bioactive fungal metabolites is important for the development of a new generation of antioxidants, antimicrobials, antiparasitic and anticancer agents.